2020
DOI: 10.3390/cancers12040873
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of PD-L1 Expression in Malignant Salivary Gland Tumors as Assessed by Established Scoring Criteria: Tumor Proportion Score (TPS), Combined Positivity Score (CPS), and Immune Cell (IC) Infiltrate

Abstract: Background: Malignant neoplasms of the salivary glands are rare, and therapeutic options are limited. Results from recently published studies indicate a possible use for checkpoint inhibition in a subset of patients, but there are no established criteria for programme cell death ligand 1 (PD-L1) scoring in salivary gland carcinomas (SGCs). Methods: In this retrospective study, we present a cohort of 94 SGC patients with full clinical follow-up. We included 41 adenoid cystic carcinomas (AdCC), 21 mucoepidermoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…Moreover, SIRPα + , CD8 + , and FOXP3 + cells were counted per high power field in five dependent fields for each case. This process was based on previous studies, with modifications 32 , 33 , 49 51 . Statistically, the median numbers of SIRPα + , CD8 + , and FOXP3 + cells were determined as the cut-off points.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, SIRPα + , CD8 + , and FOXP3 + cells were counted per high power field in five dependent fields for each case. This process was based on previous studies, with modifications 32 , 33 , 49 51 . Statistically, the median numbers of SIRPα + , CD8 + , and FOXP3 + cells were determined as the cut-off points.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Vital et al, where 1% cutoff for PD-L1 (clone SP142) positivity was applied, the authors identified 13% of PD-L1 positive AciCCs and 20% of tumours with PD-L1 positive infiltrating immune cells [ 29 ]. Witte et al evaluated PD-L1 (clone SP263) expression in 16 AciCCs and described a median TPS of 1% and CPS of 3.5 in AciCCs, which was low compared to other salivary gland carcinomas PD-L1 [ 27 ]. The present study evaluating a cohort of 36 AciCCs observed comparable results of PD-L1 expression with PD-L1 28-8 clone.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with other studies examining PD-L1 expression in mixed cohorts of salivary gland carcinomas. Witte et al reported a significant association between CPS and lymph node metastasis in salivary gland carcinomas [ 27 ] and Vital et al reported that PD-L1 expression in tumour cells and TILs in salivary gland carcinomas were related to higher tumour grading [ 29 ]. Higashino et al found, that PD-L1 expression in parotid carcinomas was associated with a higher-stage, higher-grade and node positive cases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IC-Score % [inflammatory cell score (stained inflammatory cells/tumour surface)] 4. CPS (combined positivity score [(stained tumour cells + stained mononuclear immune cells)/tumour cells)] ( 21 23 ). Although the tumour showed a moderate baseline infiltration of CD8+ cytotoxic T-cells (intratumoral CD8+ before pembrolizumab: 756 CD8+ T-cells per mm2) and PD-L1 expression on tumour (TPS 55%, CPS 70) and immune cells (IC-Score 15%), Pembrolizumab treatment led to a significant increase of CD8 infiltration with a very strong increase of intraepithelial localized CD8+ cytotoxic T-cells (intratumoral: 2221 CD8+ T-cells per mm2) and a strong upregulation of PD-L1 expression on tumour cells (TPS 100%, CPS 100) as well as on tumour infiltrating immune cells (IC-Score 40%; Figures 3A, B ) .…”
Section: Histopathological Findingsmentioning
confidence: 99%